Moving to restoration: How can service providers better help women in the “sex industry”? - Gonzalez, Nicole M. (Kansas State University, 2017)
The purpose of this thesis is to learn from human trafficking survivors about how service providers can better help female victims of human trafficking. The paper is guided by two theories, i.e., Attention Restoration Theory (Hartig, Evans, Jamner, Davis, & Galing, 2003) and The Holistic Process Theory of Healing (Ventegodt, Andersen, & Merrick, 2003). In this paper, I refer to the participants in my research as survivors and individuals who have been or currently are victims of human trafficking as victims. To utilize the common language used by the participants of this study, sex trafficking will be referred to as the “sex industry”. The purpose of the study was to gain the perspectives of women in the process of exiting from the sex industry to answer the overarching questions of how service providers can better help women who are on the path to restoration and recovery, as well as to help service providers better identify female victims and their needs. A combined approach of Braun and Clarke’s (2006) thematic analysis and Gilligan, Spencer, Weinberg and Bertsch’s (n.d.) Listening Guide was used to analyze the transcribed interviews for a better understanding of the narratives of the participants and the themes that emerged from their narratives.
Keywords: Human trafficking; Sex trafficking; Domestic sex trafficking; Marriage and family therapy and human trafficking; Family therapy and sex trafficking; Restoration services and sex trafficking